2012
DOI: 10.1126/science.1217876
|View full text |Cite
|
Sign up to set email alerts
|

An Abundance of Rare Functional Variants in 202 Drug Target Genes Sequenced in 14,002 People

Abstract: Rare genetic variants contribute to complex disease risk; however, the abundance of rare variants in human populations remains unknown. We explored this spectrum of variation by sequencing 202 genes encoding drug targets in 14,002 individuals. We find rare variants are abundant (one every 17 bases) and geographically localized, such that even with large sample sizes, rare variant catalogs will be largely incomplete. We used the observed patterns of variation to estimate population growth parameters, the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
659
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(733 citation statements)
references
References 81 publications
55
659
3
8
Order By: Relevance
“…It has been postulated that these rare variants, which can be detected by nextgeneration sequencing (NGS) techniques, may confer very large effect sizes (OR greater than 5) and be the primary drivers of common diseases [115,116]. Furthermore, rare coding variations often have more obvious functional impact and, therefore, could hasten the translation of genetic associations into biological understanding [117]. More recent GWAS in larger sample sizes and/or using more recent chip arrays have also shown that other loci are associated with steatosis in NAFLD [13,70] by investigating variants of intermediate frequency (MAFs falling between 1% and 5%).…”
Section: Key Pointmentioning
confidence: 99%
“…It has been postulated that these rare variants, which can be detected by nextgeneration sequencing (NGS) techniques, may confer very large effect sizes (OR greater than 5) and be the primary drivers of common diseases [115,116]. Furthermore, rare coding variations often have more obvious functional impact and, therefore, could hasten the translation of genetic associations into biological understanding [117]. More recent GWAS in larger sample sizes and/or using more recent chip arrays have also shown that other loci are associated with steatosis in NAFLD [13,70] by investigating variants of intermediate frequency (MAFs falling between 1% and 5%).…”
Section: Key Pointmentioning
confidence: 99%
“…This missing heritability problem has led to increasingly skeptical views of the common disease-common variant (CD-CV) hypothesis which predicts that common disease-causing alleles, or variants, will be found in all human populations that manifest a given disease. On the other hand, interest in studies on rare variants with minor allele frequencies less than 1% is growing [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…Chroniques génomiques [9], par l'acronyme SNV (pour single nucleotide variant), le terme de snip ou SNP (single nucleotide polymorphism) étant réservé à ceux dont l'allèle mineur a une fréquence supérieure à 5 %. Les snip (ou SNP) sont donc aussi des SNV, l'inverse n'étant pas nécessairement vrai.…”
Section: Bertrand Jordanunclassified
“…Les snip (ou SNP) sont donc aussi des SNV, l'inverse n'étant pas nécessairement vrai. Le deuxième article [9] s'est limité à 202 gènes considérés comme des cibles de médicaments, mais les a lus chez plus de 14 000 individus à une redondance moyenne de 27. Dans les deux cas, la qualité des données est évidemment essentielle : il ne s'agit pas de prendre des erreurs de séquence pour des SNV !…”
Section: Bertrand Jordanunclassified
See 1 more Smart Citation